'A fiction of long standing': Techniques of prospection and the role of positivism in US Cold War social science, 1950–65. (October 2016) - Dayé, Christian
There appears to be a widespread belief that the social sciences during the 1950s and 1960s can be characterized by an almost unquestioned faith in a positivist philosophy of science. In contrast, the article shows that even within the narrower segment of Cold War social science, positivism was not an unquestioned doctrine blindly followed by everybody, but that quite divergent views coexisted. The article analyses two 'techniques of prospection', the Delphi technique and political gaming, from the perspective of a comprehensive set of ideas attributed to 'positivism'. Both techniques were developed in the early 1950s by researchers at the RAND Corporation, a Californian think tank with tight relations to the US Air Force. Despite the closeness of origin, the two techniques show considerable differences in their basic epistemologies. The article thus concludes that more important than positivism in uniting US Cold War social science was the shared sense of urgency and of the potential of social science to put decision-making in foreign policy on a rational basis. In this sense, as far as the Cold War social sciences were of a piece, they were made so by the sense of danger and urgency of action evoked by the image of the Iron Curtain.